ANALISIS YURIDIS PENYIDIKAN TINDAK PIDANA PORNOGRAFI BERDASARKAN UNDANG-UNDANG NOMOR 44 TAHUN 2008 DI ERA DIGITALISASI - Andri Winjaya Laksana; Suratman Suratman (Jurnal Pembaharuan Hukum, 2014)
Pornography is a crime that is privacy so that enforcement against the eradication of pornography there are many difficulties. One of the factors inhibiting the eradication of pornography among others due to lack of cooperation from the public and the various parties in reporting this crime. Criminal law enforcement have a tendency to be influenced by the structure of society, that is a constraint that allows the criminal law enforcement can be run and can provide barriers that lead to the enforcement of criminal law can’t be started or can't be maximize. As happens to the pros cons on current legislation Law No. 44 Year 2008 concerning the Crime pornography. This research method using normative juridical approach. Normative juridical research also called legal research library research is done by checking library materials or secondary data. The results of the study refers to Article 34 in conjunction with Article 8 of Law No. 44 Year 2008 on Pornography, (1) that the elements of the crime of pornography consists of Subjective elements that error, which means intentionally or consent was committed and objective elements that act ( be) which means that objects or models that contain pornographic content. (2) In the process of criminal investigations conducted pornography remains based on Criminal Procedure unless otherwise provided in the Act No. 44 of 2008